Banking Flows and Financial Crisis : Financial Interconnectedness and Basel III Effects - Ghosh, Swati R.; Sugawara, Naotaka; Zalduendo, Juan (2012)
This paper examines the factors that determine banking flows from advanced economies to emerging markets. In addition to the usual determinants of capital flows in terms of global push and local pull factors, it examines the role of bilateral factors, such as growth differentials and economic size, as well as contagion factors and measures of the depth in financial interconnectedness between lenders and borrowers. The analysis finds profound differences across regions. In particular, in spite of the severe impact of the global financial crisis, banking flows in emerging Europe stand out as a more stable region than is the case in other developing regions. Assuming that the determinants of banking flows remain unchanged in the presence of structural changes, the authors use these results to explore the short-term implications of Basel III capital regulations on banking flows to emerging markets.